2020
DOI: 10.1051/0004-6361/202039028
|View full text |Cite
|
Sign up to set email alerts
|

ClG 0217+70: A massive merging galaxy cluster with a large radio halo and relics

Abstract: We present an analysis of archival Chandra data of the merging galaxy cluster ClG 0217+70. The Fe XXV Heα X-ray emission line is clearly visible in the 25 ks observation, allowing a precise determination of the redshift of the cluster as z = 0.180 ± 0.006. We measure kT500 = 8.3  ±  0.4 keV and estimate M500 = (1.06 ± 0.11) × 1015 M⊙ based on existing scaling relations. Correcting both the radio and X-ray luminosities with the revised redshift reported here, which is much larger than previously inferred based … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 50 publications
1
26
1
Order By: Relevance
“…However, within 640 kpc, the radial profile is roughly constant although there is a hint of spectral flattening. We note that X-ray SB discontinuities are detected at the edges of the northern and southern regions (within 640 kpc) (Zhang et al 2020). Although the nature of the X-ray discontinuities (i.e.…”
Section: Spectral Index Variationsmentioning
confidence: 63%
See 3 more Smart Citations
“…However, within 640 kpc, the radial profile is roughly constant although there is a hint of spectral flattening. We note that X-ray SB discontinuities are detected at the edges of the northern and southern regions (within 640 kpc) (Zhang et al 2020). Although the nature of the X-ray discontinuities (i.e.…”
Section: Spectral Index Variationsmentioning
confidence: 63%
“…A recent study by Zhang et al (2020) found discontinuities in the X-ray SB towards the N and S edges of the radio halo in the VLA 1.4 GHz data. In addition to the two reported edges, we note that the NE edge of the radio halo in the LOFAR 141 MHz map (Fig.…”
Section: The Ne Edgementioning
confidence: 84%
See 2 more Smart Citations
“…The other two galaxy clusters found to be significant outliers are A1213(Giovannini et al 2009) and CLG 0217+70(Brown et al 2011) Zhang et al (2020). recently demonstrate that by adopting a new revised redshift estimate, the galaxy cluster CLG 0217+70 is not anymore overluminous in radio compared to X-ray, while the case of A1213 is still under investigation.…”
mentioning
confidence: 95%